PERAN KARYAWAN FRONTLINER DALAM MEMBERIKAN ASSURANCE (JAMINAN) LAYANAN: STUDI KUALITATIF DI RESTORAN THE EATERY MEDAN - Banjarnahor, Susy Christina; Fazira, Aziza (Mount Hope Management International Journal, 2025)
This qualitative research examines the role of frontliner employees in providing service assurance at The Eatery Restaurant, in Medan. Data were collected through in-depth interviews, observations, and document analysis. The findings show employees understand and strive to provide assurance (competence, courtesy, credibility, safety). However, waiters' lack of responsiveness proved to significantly erode customers' perception of service assurance, indicating the interconnectedness of quality dimensions. High workload during peak hours is a constraint. This research enriches the literature with in-depth qualitative insights into how assurance is formed and its challenges. Practical recommendations include optimizing staff schedules, integrated responsiveness training, and strengthening supervision to improve service assurance and customer satisfaction.